Bringing Rationality to Rationing?—The Challenges of Organ Allocation. Issue 4 (April 2016) - Neuberger, James
Abstract : This commentary elegantly analyzes the tradeoffs involved in any organ allocation system, providing positive feedback for the new US kidney allocation policy implemented in December 2014. It also highlights that pharmacoeconomic analyses should always be included in healthcare decisions.